STAGES OF DEVELOPMENT OF THE ACCESS OF NEW MEDICATIONS AND HEALTH TECHNOLOGIES (Retracted) - V.V. Omel'yanovskii; M.Yu. Frolov (Педиатрическая фармакология, 2011)
Retracted.The reimbursement system for drugs and medical devices is a significant factor that defines their accessibility and affordability. Due to increasing prices in healthcare worldwide, the last decades are characterized by the infusion of innovative approaches to cost-containment in healthcare and by the restriction of the ineffective or insufficiently effective technologies utilization. The requirements for including new drugs and medical devices into reimbursement lists have increased. Evidence of cost-effectiveness and budget impact of new technologies is more and more often required when dossier for health technology assessment (HTA) is submitted. The history of approaches and requirements to clinical and economical analysis from the regulatory authorities’ point of view are considered in the article. Key words: reimbursement system for drugs and medical devices, restrictive lists, effectiveness of medical technologies, appraisal of new technologies, budget impact analysis, HTA dossier. (Pediatric pharmacology. — 2011; 8 (6): 6–10).